Literature Review: Chlorogenic Acid Content Analysis With Uv-Vis Spectrophotometry In Coffee Seeds, Balegede Village, Naringgul District, Cianjur Regency - Sri Wahyuni (International Journal of Education, Information Technology, and Others, 2022)
Coffee in Indonesia has an important role as a source of foreign exchange for the country because it has high economic value. One of the regions in Indonesia as a producer of robusta coffee is Cianjur district. Naringgul village is one part of the Cianjur district which produces coffee as a commodity. Geographically, the location of Naringgul Village is very suitable for the development of coffee plants. Many Naringgul people become coffee farmers as a livelihood without knowing the advantages of the content in the coffee they produce. The question in this study is what are the components of active chemical compounds contained in the coffee beans of Naringgul village as the mainstay of coffee production. The method used is a literature review journal by looking for several journals related to the research title. Search journals through google scholarships from national, international journals, textbooks and scientific articles. The analytical method to determine the components of the active chemical compounds in coffee beans is the UV-Vis spectrophotometry method. The results of the review obtained are the components of active chemical compounds in coffee beans in general are chlorogenic acid, aromatic compounds, pyrolles, mercaptans, phenols, Thiophenes, Furans, and Pyrazines. Based on the results of the analysis, it was found that the highest levels of chlorogenic acid were found in coffee beans that had gone through a certain roasting process.